A historical archaeology of early Spanish colonial urbanism in Central America - Fowler, William R. (William Roy), 1950- (University Press of Florida, 2022)
"In this milestone work, William Fowler uses archaeology, history, and social theory to show that the establishment of cities was essential to Spanish colonialism. Fowler draws upon decades of research at Ciudad Vieja, a sixteenth-century site located in present-day El Salvador and the best-preserved Spanish colonial city in Latin America"--